Cooperative Financial Management at Al-Hidayah Islamic Boarding School (Pondok Pesantren Al-Hidayah ) in Batu City - Dafrosa Virginia Nganur; Cakti Indra Gunawan; Fitria Setyaningrum (IRDH International Journal of Social Sciences & Humanities, 2026)
This study aimed to analyze and comprehensively describe the financial management of the cooperative at Al-Hidayah Islamic Boarding School in Batu City. As an Islamic educational institution, pesantren played an important role in improving economic development through the establishment of cooperatives, commonly known as kopontren. This cooperative contributed to enhancing students’ welfare and supporting institutional development. The study employed a descriptive qualitative approach, and data were collected through observation, documentation, and structured interviews with relevant stakeholders, including pesantren leaders and cooperative administrators. The findings indicated that the Al-Hidayah Islamic Boarding School Cooperative had undergone significant changes since its establishment in 1995. Initially, the cooperative functioned merely as a formality with simple management under the supervision of its founder. However, since 2020, the cooperative had been reactivated as a productive unit providing savings and loan services for teachers and selling basic necessities. Despite its operations, the cooperative’s financial management still faced challenges, particularly due to limited skilled human resources and ineffective management practices, including the lack of clear separation between pesantren funds, cooperative operational funds, and members’ income. Nevertheless, religious values and Islamic economic principles were implemented in daily operations, such as the “honesty canteen” system and transparent profit margin management. Overall, although improvements in professionalism and legal compliance were still needed, the cooperative had become a crucial pillar in supporting financial stability and educational development at Al-Hidayah Islamic Boarding School